Montelukast inhibits caspase-3 activity and ameliorates oxidative damage in the spinal cord and urinary bladder of rats with spinal cord injury - ŞENER, AZİZE; YEGEN, BERRAK; AKAKIN, DİLEK; ŞENER, GÖKSEL (ELSEVIER SCIENCE INC, 2012)
Spinal cord injury (SCI) leads to an inflammatory response that generates substantial secondary damage within the tissue besides the primary damage. Leukotrienes are biologically active 5-lipoxygenase products of arachidonic acid metabolism that are involved in the mediation of various inflammatory disorders including SCI. In this study, we investigated the possible protective effects of montelukast, a leukotriene receptor blocker, on SCI-induced oxidative damage. Wistar albino rats (n = 24) were divided randomly as control, vehicle- or montelukast (10 mg/kg, ip)-treated SCI groups. To induce SCI, a standard weight-drop method that induced a moderately severe injury at T10 was used. Vehicle or montelukast were administered to the injured animals 15 min after injury. At seven days post-injury, neurological examination was performed and rats were decapitated. Blood samples were taken to evaluate leukotriene 134 levels, and pro-inflmamatory cytokines (TNF-alpha, IL-1 beta) while in spinal cord and urinary bladder samples malondialdehyde (MDA), glutathione (GSH), luminol chemiluminescence (CL) levels and myeloperoxidase (MPO) and caspase-3 activities were determined. Tissues were also evaluated histologically. SCI caused significant decreases in tissue GSH, which were accompanied with significant increases in luminol CL and MDA levels and MPO and caspase-3 activities, while pro-inflammatory cytokines in the plasma were elevated. On the other hand. montelukast treatment reversed these parameters and improved histological findings. In conclusion, SCI caused oxidative tissue injury through the activation of pro-inflammatory mediators and by neutrophil infiltration into tissues, and the neuroprotective and antiapoptotic effects of montelukast are mediated by the inhibition of lipid peroxidation, neutrophil accumulation and proinflammatory cytokine release. Moreover, montelukast does not only exert antioxidant and antiapoptotic effects on the spinal cord, but it has a significant impact on the bladder tissue damage secondary to SCI. (C) 2012 Elsevier Inc. All rights reserved.
Keywords: Oxidative stress; Spinal cord injury; Caspase-3; Bladder; Leukotriene; Montelukast; RECEPTOR BLOCKER MONTELUKAST; FOCAL CEREBRAL-ISCHEMIA; TRAUMATIC BRAIN-INJURY; NEUROLOGICAL DYSFUNCTION; SECONDARY INJURY; CELL-DEATH; INFILTRATION; INFLAMMATION; ANTAGONIST; APOPTOSIS